Is the impact of atopic disease on children and adolescents’ health related quality of life modified by mental health?: results from a population-based cross-sectional study - Matterne, Uwe; Apfelbacher, Christian (Health and quality of life outcomes, 2013)
Eczema, asthma and hay fever are global health problems and their prevalence has increased considerably over the last decades. All appear to share an underlying atopic diathesis but their aetiology is considered to be multifactorial. They have been linked to decreases in health related quality of life (HRQoL) in adults, children/adolescents and/or parents of children. Research also suggests an association of the three conditions with mental health, which in turn is related to HRQoL decreases. We aimed to assess whether the impact of any of the three conditions on HRQoL is modified by presence of mental health problems.
Gesehen am 25.06.2021